Emerging and Reemerging Diseases in the World Health Organization (WHO) Eastern Mediterranean Region—Progress, Challenges, and WHO Initiatives - Buliva, Evans; Elhakim, Mohamed; Tran Minh, Nhu Nguyen; Elkholy, Amgad; Mala, Peter; Abubakar, Abdinasir; Malik, Sk Md Mamunur Rahman (Frontiers in Public Health, 2017)
The Eastern Mediterranean Region (EMR) of the World Health Organization (WHO) continues to be a hotspot for emerging and re-emerging infectious diseases and the need to prevent, detect and respond to any infectious diseases that pose a threat to global health security remains a priority. Many risk factors contribute in the emergence and rapid spread of epidemic diseases in the Region including acute and protracted humanitarian emergencies resulting in fragile health systems, increased population mobility, rapid urbanization, climate change, weak surveillance and limited laboratory diagnostic capacity, and increased human–animal interaction. In EMR, several infectious disease outbreaks were detected, investigated and rapidly contained over the past five years including: yellow fever in Sudan, Middle East respiratory syndrome in Bahrain, Oman. Qatar, Saudi Arabia, United Arab Emirates and Yemen, cholera in Iraq, avian influenza A (H5N1) infection in Egypt, and dengue fever in Yemen, Sudan and Pakistan. Dengue fever remains an important public health concern, with at least eight countries in the region being endemic for the disease. The emergence of MERS-CoV in the region in 2012, and its continued transmission currently poses one of the greatest threats. In response to the growing frequency, duration and scale of disease outbreaks, WHO has worked closely with member states in the areas of improving public health preparedness, surveillance systems, outbreak response, and addressing critical knowledge gaps. A Regional network for experts and technical institutions has been established to facilitate support for international outbreak response. Major challenges are faced as a result of protracted humanitarian crises in the region. Funding gaps, lack of integrated approaches, weak surveillance systems, and absence of comprehensive response plans are other areas of concern. Accelerated efforts are needed by Regional countries, with the continuous support of WHO, to build and maintain a resilient public health system for detection and response to all acute public health events.